The Influence of Competency-Based Training on the Readiness of Nautical Cadets in the Maritime Industry - Suprapti, Fitri (Journal of Education Research, 2024)
The global maritime industry is experiencing rapid development, leading to an increased demand for a highly skilled and competent workforce. In response, competency-based training has become a crucial approach to prepare Nautical Cadets for the challenges they face. This study aims to explore the role of competency-based training in enhancing the readiness of Nautical Cadets for the maritime industry, particularly in meeting international standards such as STCW. The research employs a quantitative descriptive approach, collecting data through structured questionnaires from 100 cadets. The analysis results show that competency-based training significantly contributes to cadet readiness, with an improvement of 58% (R-Square = 0.58). The study also highlights the development of technical skills, soft skills, and the cadets' ability to manage work-related stress. These findings emphasize the importance of continuous training programs to equip cadets with the necessary skills for the global maritime workforce. However, the study acknowledges limitations, such as the exclusion of variables like sea experience and institutional support, which should be considered in future research for a more comprehensive perspective.